Velocity Vector Control of a Linear Permanent Magnet Synchronous Motor - Vladimir Vavrus; Jan Vittek; Michal Malek (Communications - Scientific letters of the University of Zilina, 2007)
The paper presents a design of vector control algorithm for electric drive employing a linear permanent magnet synchronous motor (LPMSM). For simulation and further experimental verification it was necessary to formulate a mathematical model of the LPMSM. This model was derived from a standard mathematical model of a rotary PMSM and then exploited to verify vector control of the machine. The presented simulation results are used to control the LPMSM drive system with maximum efficiency.